Factors Influencing Consumer Purchase Intention and Adoption Onwards of 5G Mobile Phone in Malaysia - Hoo, Wong Chee; Ping, Lim Shuk; Hossain, Syed Far Abid; Jia, Ye; Razak, Dzuljastri Abdul (Journal of Ecohumanism, 2024)
The use of 5G technology signifies a significant progression in mobile telecommunications, offering improved speed, connection and efficiency. The objective of this research is to determine the variables that impact customer purchase intention and subsequent adoption of 5G mobile phones, specifically from the viewpoint of popular shopping platforms in Malaysia. The theoretical framework can be found pursuant to the Technology Acceptance Model (TAM) and the Diffusion of Innovations (DOI) theory. Utilising quantitative surveys to collect extensive data from a varied sample of Malaysian customers who are Shopee subscribers. A total of 413 samples was successfully collected using convenience sampling of Malaysians in the Klang Valley. Findings suggest that factors such as perceived ease of use, subjective norm, and attitude serve a crucial role in determining purchase intention. The online purchasing of 5G mobile phones is greatly influenced by both intention and actual behaviour. The study emphasises the need of using targeted marketing tactics that specifically target these diverse characteristics. Online merchants and mobile phone manufacturers may greatly boost customer trust and adoption rates by improving user experience, offering comprehensive product information, and implementing strong security measures. The study offers vital information for competitors seeking to take advantage of the continuously growing 5G industry in Malaysia.